Responses of Water and Pigments Status, Dry Matter Partitioning, Seed Production, and Traits of Yield and Quality to Foliar Application of GA3 in Mungbean (Vigna radiata L.) - Islam, Mohammad Sohidul; Hasan, Md. K.; Islam, Bushra; Renu, Nowrin Akhter; Hakim, Mohammad A.; Islam, Mohammad Rafiqul; Chowdhury, M. Kaium; Ueda, Akihiro; Saneoka, Hirofumi; Ali Raza, Muhammad; Fahad, Shah; Barutçular, Celaleddin; et al. (Frontiers in Agronomy, 2021)
In this context, a field experiment was conducted to evaluate the effects of GA3 on water status, dry matter partitioning, yield traits, seed production and quality of traits mungbean varieties. Two varieties (BARI Mung-6 and BARI Mung-8), and four doses of GA3 (0 ppm, 100 ppm, 200 ppm and 300 ppm) were used in this experiment. The result of relative water content (water status in plant) in leaves was influenced by the foliar application of GA3, and the highest value was obtained with the 200 ppm of GA3. The variety BARI Mung-8 maintained better water content in plants than BARI Mung-6 under GA3 treatments. Biomass weight in different plant organs i.e. fresh and dry weights of leaves, petioles, stems and roots were increased with the foliar spraying of GA3, and the increment was mountained at 200 ppm GA3 levels, and thereafter decreased. GA3 induced higher partitioning of biomass in different plant parts of BARI Mung-8 than that of BARI Mung-6. Yield contributing traits like plant height (cm), number of pods plant-1, number of grains pod-1, pod length (cm), and 100 grain weight (g) were also reacted positively by the application of GA3 in both varieties in this study, and BARI Mung-8 was more responsive to GA3 than BARI Mung-6. Yield contributing traits reflect the grain yield (tha-1), stover yield (tha-1) and harvest index (%), and spraying of GA3 increased those traits in both varieties as well as due to the ultimate consequence of yield traits. The results of yield and harvest index of BARI Mung-8 were superior to BARI Mung-6 under GA3 treatments. Application of GA3 @ 200 ppm significantly produced the highest aforesaid yield traits, yield and harvest index of mungbean varieties among the different concentration of GA3. Considering the quality traits, GA3 positively influenced on nitrogen and protein content in grains and spraying of 200 ppm was found more profound among all treatments. Therefore, BARI Mung-6 and BARI Mung-8 can be grown with the foliar sparing of 200 ppm GA3 (before and after flowering) for obtaining higher yield and grain protein content, and BARI Mung-8 should be selected